Grassmann techniques applied to classical spin systems - Clusel, M.; Fortin, J.-Y. (Condensed Matter Physics, 2009)
We review problems involving the use of Grassmann techniques in the field of classical spin systems in two dimensions. These techniques are useful to perform exact correspondences between classical spin Hamiltonians and field-theory fermionic actions. This contributes to a better understanding of critical behavior of these models in term of non-quadratic effective actions which can be seen as an extension of the free fermion Ising model. Within this method, identification of bare masses allows for an accurate estimation of critical points or lines and which is supported by Monte-Carlo results and diagrammatic techniques. Ми оглядаємо задачi, у яких використовуються грасмановi технiки для класичних спiнових систем у двох вимiрах. Цi технiки є корисними для встановлення точної вiдповiдностi мiж класичними спiновими гамiльтонiанами i теоретико-польовими фермiонними дiями. Це дає змогу краще зрозумiти критичну поведiнку цих моделей у термiнах неквадратичних ефективних дiй, на якi можна дивитися, як на розширення вiльнофермiонної моделi Iзинга. У межах цього методу iдентифiкацiя затравочної маси дозволяє виконати точну оцiнку критичних точок чи лiнiй, що пiдтверджується результатами Монте Карло чи дiаграмних технiк.